Factors related to self-care practice in asthmatic patients at rajshahi in Bangladesh (Bangladesh Journal of Medical Science, 2018)
Background: This descriptive correlation study was aimed to examine factors related to selfcare practice in asthmatic patients at Rajshahi in Bangladesh.Methods: A total of 126 asthmatic patients who met the inclusion criteria were selected by simple random sampling technique during March to April, 2014. The research instruments consisted of four parts: The Demographic Questionnaire, The Asthmatic Self-Care Practice Questionnaire, The Attitude of Asthmatic Questionnaire, and The Knowledge of Asthmatic Questionnaire. KR-20 for the reliability of Knowledge Questionnaire was yielded at 0.76 and the Cronbach’s alpha coefficient of Attitude and Self-Care Practice Questionnaire were 0.74 and 0.75 respectively. Data were analyzed using descriptive statistics and Pearson’s correlation coefficient.Result: The results of the study illustrated that the total mean score of self-care practice in asthmatic patients was 49.63 (S.D = 9.5). The mean total score of attitude was 72.46 (S.D =9.27) and the total mean score of knowledge was 11.80 (S.D = 4.42). There was a moderate positive significant correlation between attitude and self-care practice (r =0.49, p < 0.01). Additionally, there was a moderate positive significant correlation between knowledge and self-care practice (r = 0.30, p < 0.01).Conclusion: The findings suggested that nurses should conduct health education programs to increase knowledge and promote positive attitude about self-care practice in asthmatic patients.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.57-62